2010
DOI: 10.1007/s10926-009-9227-7
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Health Understandings and Processes in Small Businesses: A Systematic Review of the Qualitative Literature

Abstract: This synthesis details the unique qualities and conditions of SBs that merit particular attention from planners and occupational health policy makers. In particular, the informal workplace social relations can limit workers' and employers' apprehension of risk, and policy and complex contractual conditions in which SBs are often engaged (such as chains of subcontracting) can complicate occupational health responsibilities. This review questions the utility of SB exemptions from OHS regulations and suggests a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 40 publications
2
62
0
1
Order By: Relevance
“…This production-oriented perspective on work ability became apparent when economic goals and costs were stressed as factors that influenced employers" ability to make accommodations. These findings are in accordance with other studies that underline employers" cost concerns regarding return to work measures or hiring people with disabilities [29][30]. Meanwhile, previous research shows a relation between company size and the presence of return to work measures.…”
Section: Employers' Impact On Work Abilitysupporting
confidence: 92%
See 1 more Smart Citation
“…This production-oriented perspective on work ability became apparent when economic goals and costs were stressed as factors that influenced employers" ability to make accommodations. These findings are in accordance with other studies that underline employers" cost concerns regarding return to work measures or hiring people with disabilities [29][30]. Meanwhile, previous research shows a relation between company size and the presence of return to work measures.…”
Section: Employers' Impact On Work Abilitysupporting
confidence: 92%
“…Indeed, a lack of health and safety resources and a lack of clear local policies for managing early return to work can result in solutions based on expense avoidance rather than on work rehabilitation. Employers tend to focus on their own business and production logic [29].…”
Section: Employers' Impact On Work Abilitymentioning
confidence: 99%
“…This tension between social responsibility and economic interests has been observed in previous research [12,19,[38][39][40][41]. One study identified how employers experienced a conflict of interest between their formal role of implementing an early-return-to-work policy and their need to consider their production demands [39].…”
Section: Employers' Economic Perspective On Return To Work In the Conmentioning
confidence: 85%
“…Furthermore, the need for early contact and regular communication between supervisor and sick-listed employee, as well as multi-stakeholder collaboration is highlighted [11][12][13][14]. Research has also shown that lack of clear local policies for managing early return to work may result in solutions based on expense avoidance rather than on rehabilitation to work when employers tend to focus on their own business and production logic [19].…”
Section: Introductionmentioning
confidence: 99%
“…WHM is rarely addressed in small business research [17][18][19][20]. WHM is crucial for improvements in psychosocial working conditions and health [21], but few studies explore the challenges SSEs experience regarding these issues and which contextual factors can contribute to improvements.…”
Section: Introductionmentioning
confidence: 99%